Trilogy of COVID-19, Climate, and the Russian-Ukrainian War: The Impact on Food Security in Arab Countries - اسبر, ميساء (Latakia University Journal - Economic and Legal Sciences Series, 2022)
After years of development and attempts to reduce the number of poor and people who are food insecure, the world witnessed successive strikes that started with the spread of the Covid epidemic and its exit from the borders of China to become a global epidemic, and then climate problems around the world and recently the Russian-Ukrainian war. All of this represented a global food security stress, which it becomes global issue and includes the most countries in different degrees. The Arab countries had a large share of this stress, including Syria, due to the war in Syria, which greatly exacerbated the situation. This prompted international organizations to prepare more for this danger and to come up with policies and procedures to reduce risks. Whereas, the research sought to study how the Covid epidemic, climate and the Russian-Ukrainian war affected global food security in Arab countries, including Syria, and reached a set of recommendations and proposals.